MENINGKATKAN KEMAMPUAN BERBAHASA EKSPRESIF ANAK MELALUI METODE BERNYANYI - Tita Juwita; Anwar Rifai; Dita Handayani (LPPM Universitas Bina Bangsa, 2022)
The tests, observations, and documentation were used as a data collection technique. The research subjects were 16 children from group A at KB AL-IQRO, Cilengkrang District, Bandung Regency. The expressive language skills research through the singing method in the learning process has increased. The singing method is used to create the atmosphere more pleasant, improve vocabulary, and obey the rules when the learning process is in progress. The purpose singing method of implementing CAR is 1) to understand children's expressive language skills, 2) to know the process of applying the singing method able to improve children's expressive language skills, 3) to know the improvement of expressive language skills after applying the singing method. Recommendations for group A teachers’ are to search for more references to musical songs and instruments